2013
DOI: 10.1002/jame.20043
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of tropical cumulus congestus during TOGA COARE

Abstract: [1] Recent observational studies of tropical deep convection typically include some mention of cumulus congestus, a third mode of tropical convection, in addition to shallow trade cumulus and deep convection. This study analyzes congestus behavior in a multiday cloud-resolving model simulation based on the Tropical Ocean-Global Atmosphere Coupled Ocean-Atmosphere Response Experiment (TOGA COARE) field campaign. Simulation results exhibit a pronounced congestus cloud mode, present during both suppressed and act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 71 publications
(112 reference statements)
1
19
0
Order By: Relevance
“…Previous studies have reported this correlation to be related to the characteristics of stratiform/convective rainfall types associated with MCSs [ Kurita et al ., ; Kurita , ], but we propose to explore this relationship as the in‐cloud temperature effects. In the tropics, the lower (higher) OLR values may reflect the higher (lower) cloud top and echo top altitudes of storm systems, with precipitation forming at cooler (warmer) temperatures in clouds [e.g., Mechem and Oberthaler , , Figure 5]. Hence, positive correlations between rainfall δ 18 O and OLR values can also be interpreted with respect to the temperature effect at the mean condensation level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported this correlation to be related to the characteristics of stratiform/convective rainfall types associated with MCSs [ Kurita et al ., ; Kurita , ], but we propose to explore this relationship as the in‐cloud temperature effects. In the tropics, the lower (higher) OLR values may reflect the higher (lower) cloud top and echo top altitudes of storm systems, with precipitation forming at cooler (warmer) temperatures in clouds [e.g., Mechem and Oberthaler , , Figure 5]. Hence, positive correlations between rainfall δ 18 O and OLR values can also be interpreted with respect to the temperature effect at the mean condensation level.…”
Section: Discussionmentioning
confidence: 99%
“…In cloudy conditions, this reflects the altitude of the cloud top. Therefore, in the tropics, lower (higher) OLR values also correspond to higher (lower) cloud top and echo top altitudes, average altitude of rainfall within clouds, and likely associated with cooler (warmer) temperatures at which precipitation forms in clouds [e.g., Mechem and Oberthaler , , Figure 5]. Based on echo tops radar data, previous studies in Puerto Rico and Hawaii concluded that rain δ 18 O seasonality is influenced by atmospheric temperatures (temperature effect [ Dansgaard , ]) that correspond to different cloud heights associated with the seasonal climate patterns [ Scholl et al ., ; Scholl and Coplen , ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we configure SAMEX in a manner roughly similar to that of the RICO (Rain in Cumulus over the Ocean) [ Rauber et al ., ] trade cumulus intercomparison [ van Zanten et al ., ]. For these simulations, SAMEX employs a horizontal grid spacing of 100 m and a constant vertical spacing of 50 m. Previous studies demonstrate the importance of using fine vertical grid spacing for representing cumulus congestus [ Khairoutdinov et al ., ; Mechem and Oberthaler , ]. The number of grid points is 384 × 384 × 160 to yield a domain size of 38.3 × 38.3 × 8 km 3 , a volume that captures the cloud system mesoscale variability reasonably well.…”
Section: Large‐eddy Simulationmentioning
confidence: 99%
“…; Posselt et al. ; Mechem and Oberthaler, ). With increasing SST gradient, convection over the cold ocean collapses from deep convection with tops near 150 hPa, to cumulus congestus , with tops near 550 hPa and near 650 hPa, and then to shallow cumulus, with tops near 850 hPa.…”
Section: Discussionmentioning
confidence: 60%
“…CRM simulations of radiative–convective equilibrium (RCE) and the TOGA COARE campaign reproduce the trimodality in tropical convection ((Posselt et al. ); (); (Pakula and Stephens, ; Mechem and Oberthaler, )), but GCMs have difficulties reproducing such trimodality due to poor vertical resolution (Inness et al. ) and the bimodal nature of convective parametrizations.…”
Section: Introductionmentioning
confidence: 76%